Forensic investigation in a body packer case (2015)
Purpose: To account for the problems posed by the use of narcotics in Colombia,regardless of type, person, reason or socioeconomic status. Topics: Overdose cases, treatments, guidelines for managing and approaching the issue of narcotics, or nowadays often referred to as “recreational drugs”. Development: This article refers to the case of a young woman in Armenia (Quindío, Colombia), of whom, at the time of autopsy, there was no information available to suspect that this was a case of body packer intoxication. Conclusions: These cases are rare; therefore, there is a possibility that the approach to the scene is not appropriate from the forensic-investigative point of view, which must be complete and consider items available around the scene and the circumstances surrounding the death. This is because, when addressing this case, there was not the slightest hint of suspicion that it would become a case of drug transportation or ‘mules’.